Molecular requirements for B-lymphocyte activation by Escherichia coli lipopolysaccharide. - Raetz, C R (1983)
Certain Escherichia coli mutants altered in phosphatidylglycerol metabolism accumulate fatty acyl derivatives of glucosamine 1-phosphate. Especially prominent is 2,3-diacylglucosamine 1-phosphate (previously designated lipid X), which may be an early precursor of lipid A. We have examined the activity of lipid X (Mr = 711.9) and several related compounds as mitogens towards mouse lymphocytes. As judged by labeling with [methyl-3H]thymidine, lipid X is mitogenic, and it mimics the properties of lipopolysaccharide and lipid A. The following evidence suggests that lipid X exerts its effects by a route similar to that of lipopolysaccharide: (i) lymphocytes from C3H/HeJ mice, which are unresponsive to lipopolysaccharide, are also not stimulated by lipid X; (ii) polymyxin B abrogates lymphocyte stimulation by lipid X; and (iii) lipid X induces the proliferation and maturation of lymphocytes to antibody-producing plaque-forming cells. Selective removal of the ester-linked hydroxymyristate moiety at position 3 totally abolishes mitogenic activity. Other phospholipids, such as phosphatidic acid, CDP-diglyceride, phosphatidylcholine, and lysophosphatidylcholine, have no activity as mitogens. If lipid X and lipid A induce by common mechanism(s) B-lymphocyte proliferation, then it follows from structural comparison that the reducing-end subunit of lipid A is the minimal structural requirement for this activity. Because the structure of lipid X is completely defined, biochemical and pharmacological dissection of B-cell activation by lipopolysaccharide should now be possible.